f) (2x-1)(3x-1)-(3x-2)(2x-3) = 0
g) (4-x)(2x+3)+2x² = 6
h) (2x+3)(3x-1) + 4 = (6x-2)(x+1)


Odpowiedź :

Temat: Rozwiązywanie równań

Rozwiązania poniżej ;-)

f)

[tex](2x-1)(3x-1)-(3x-2)(2x-3)=0\\\\6x^2-2x-3x+1-(6x^2-9x-4x+6)=0\\\\6x^2-5x+1-(6x^2-13x+6)=0\\\\6x^2-5x+1-6x^2+13x-6=0\\\\8x-5=0\\\\8x=5 \ \ |:8\\\\\boxed{x=\frac{5}{8}}[/tex]

g)

[tex](4-x)(2x+3)+2x^2=6\\\\8x+12-2x^2-3x+2x^2=6\\\\5x+12=6\\\\5x=6-12\\\\5x=-6 \ \ |:5\\\\\boxed{x=-1\frac{1}{5}}[/tex]

h)

[tex](2x+3)(3x-1)+4=(6x-2)(x+1)\\\\6x^2-2x+9x-3+4=6x^2+6x-2x-2\\\\6x^2+7x+1=6x^2+4x-2\\\\6x^2+7x-6x^2-4x=-2-1\\\\3x=-3 \ \ |:3\\\\\boxed{x=-1}[/tex]